If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + -15 = 18a + 1 Reorder the terms: -15 + 12a = 18a + 1 Reorder the terms: -15 + 12a = 1 + 18a Solving -15 + 12a = 1 + 18a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-18a' to each side of the equation. -15 + 12a + -18a = 1 + 18a + -18a Combine like terms: 12a + -18a = -6a -15 + -6a = 1 + 18a + -18a Combine like terms: 18a + -18a = 0 -15 + -6a = 1 + 0 -15 + -6a = 1 Add '15' to each side of the equation. -15 + 15 + -6a = 1 + 15 Combine like terms: -15 + 15 = 0 0 + -6a = 1 + 15 -6a = 1 + 15 Combine like terms: 1 + 15 = 16 -6a = 16 Divide each side by '-6'. a = -2.666666667 Simplifying a = -2.666666667
| -x-4=3x-52 | | -6t+-7=7 | | 2r(0.7+5)= | | 4x+3-8x+1=-5x+9 | | 6(3x+5)-9x=75 | | 12-3y=16-5y | | 3-5=7n+11 | | 2x+7+(2x+6)+2x=2x+(2x)+(3x)+7 | | -20=0.1x-0.5x | | 1/2(2/4) | | 188=32x+10(6) | | 2/3(12-14)=2 | | m+7+8=-28 | | x^3+9x^2+8x+72=0 | | 3(x+7)-3=54 | | 10+5-1-5b=15b+3 | | m+7+8=28 | | .20x+.25(70)=36.5 | | 2=6(2a+2) | | -4x+10=-2x+2 | | -3(2-4x)=18 | | m+4+9=-23 | | m+4+9=23 | | 2/3(-42+49)=2 | | 6x+24=10x-20 | | 6x^2-18x+0=0 | | C=2(8)-2 | | 2(3x+2)=4x+16 | | 5w-6-2w=18 | | 12b-6+2-3b=4b+5 | | 3/8x-1/4 | | m+7=-37 |